A systematic overview of Descolea ( Agaricales ) in the Nothofagaceae forests of Patagonia - Kuhar, José Francisco; Smith, Matthew E.; Mujic, Alija; Truong, Camille; Nouhra, Eduardo Ramon (Fungal Biology)
The descolea clade includes species of ectomycorrhizal basidiomycetes in the genera Descolea, Setchelliogaster, Descomyces, and Timgrovea that are known primarily from the Southern Hemisphere. Taxa in this group produce basidiomes that range in morphology from typical epigeous mushrooms (Descolea) and secotioid taxa (Setchelliogaster) to fully gasteroid species (Descomyces and Timgrovea). High intraspecific morphological variation has been reported in several species within this clade, suggesting that careful morphological and molecular studies are needed to refine species concepts. Molecular analyses of fresh Patagonian collections in conjunction with taxonomic studies have confirmed high variability in key morphological features, including overall sporocarp form, spore shape and dimensions, universal veil remnants and cuticle configuration. Based on our synthesis, we emend the genus Descolea to include sequestrate species. We describe the new sequestrate taxon Descolea inferna sp. nov. from Nothofagaceae forests in Patagonia and we propose Thaxterogaster squamatus as a synonym of our new combination Descolea brunnea. We also formalize the identity of Descolea pallida as a synonym of D. antarctica and provide new specimens of Thaxterogaster archeuretus, a species that has not been encountered since the original discovery during the expeditions of Roland Thaxter in 1905-1906. Here we re-describe and transfer this species to Descolea as D. archeureta. We also discuss diagnostic features that can be used to delimitate the four known South American taxa in the descolea clade. Fil: Kuhar, José Francisco. Centro de Investigación y Extensión Forestal Andino Patagónico; Argentina. Universidad Nacional de la Patagonia; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Smith, Matthew E. University of Florida; Estados Unidos Fil: Mujic, Alija. University of Florida; Estados Unidos Fil: Truong, Camille. University of Florida; Estados Unidos Fil: Nouhra, Eduardo Ramon. Consejo ...